Waterbirds and aquatic recreation at Lake Ijsselmeer, The Netherlands: the potential for conflict - Platteeuw, Maarten; Henkens, Rene J H G (Wildfowl, 1997)
The 170,000 ha Lake Ijsselmeer area is a stronghold for internationally important numbers of waterbirds, and is also important for aquatic recreation. Research has been undertaken to investigate potential conflicts. An inventory was made of the occurrence of recreational use in time and space, of waterbird food resources and potentially suitable roosts, and of actual use by birds. This indicated that conflicts between recreation and waterbirds were particularly likely from April to October, and involve breeding and moulting birds, and those staging in late summer. Some areas were extensively used for recreation and there was evidence that birds avoided those parts most heavily used. In one area, where conflicts were likely, detailed observations showed reduced bird abundance and distributional shifts. It is suggested that management measure aimed at maintaining both wildlife and recreation uses within the lakes, should separate spatially the core areas of these functions.